Correlation of Dengue Infection Severity with Abdominal Pain, Delta Hematocrit, Platelet Count, and Delta Hematocrit-Platelet Ratio in Pediatric Patients - Agustina, Dinda Dwi; Puspitasari, Metana; Jatmiko, Safari Wahyu (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aimed to determine the correlation between the severity of dengue infection and abdominal pain, delta hematocrit, platelet levels, and the delta hematocrit-platelet ratio. Methodology: the study used a correlational observational design with a cross-sectional approach. Data were obtained from the medical records of dengue infection patients at PKU Muhammadiyah Sampangan Hospital from October–November 2024. A total of 39 samples were selected using a consecutive non-probability sampling technique. Data analysis was performed using JASP statistical software version 0.19.1.0. Results: The study revealed no significant relationship between the severity of dengue infection and abdominal pain (p=0.089), delta hematocrit (p=0.589), platelet levels (p=0.068), or the delta hematocrit-platelet ratio (p=0.740). Applications/Originality/Value: This study provides valuable insights into the limitations of individual clinical and laboratory parameters, emphasizing the need for a comprehensive approach to assessing dengue severity in pediatric patients.